Methodological proposal for the definition of improvement strategies in logistics of SME - Becerra, Yeimy Liseth (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
A methodological proposal for defining strategies of improvement in logistics of SMEs is presented as a means to fulfill a specific objective of the project Methodological design on storage logistics, acquisition, ownership of information systems and communication for Colombian SMEs, baker subsector, which currently runs the research group SEPRO, of Universidad Nacional of Colombia and supported by Colciencias. The project corresponds to the completion of the last stage of the base project, and aims to implement the corresponding target, raised in the research project that has been developing the research group SEPRO. To do this, it was made a review of the methodology used during the execution of the basic project, as well as the state of the art of techniques used in similar research for the evaluation and definition of breeding strategies in SMEs logistics. Revised techniques were compared and a proposed methodology was configured, which consists of the techniques that represented the greatest advantages for the research development.